1980
DOI: 10.1007/bf01639888
|View full text |Cite
|
Sign up to set email alerts
|

Methodological implications of testing anaerobe susceptibility to cephalosporins (cefazolin, cefamandole, cefoxitin)

Abstract: By simultaneously performing broth dilution, agar dilution, and agar diffusion tests with Bacteroidaceae and Peptococcaceae, the influence of methodology upon the outcome of susceptibility testing to cefazolin, cefamandole and cefoxitin was studied. With beta-lactamase positive and negative Bacteroidaceae, the results of the broth dilution and agar dilution tests were in good agreement for cefoxitin. However, when tested with cefaxolin and cefamandole, beta-lactamase positive Bacteroides strains had mostly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Alamar method tended to produce lower MICs than did agar dilution if the organism was very susceptible to the ,B-lactam agent but higher MICs if the organism produced an inducible or extended-spectrum r-lactamase. Other investigators have reported this dichotomous effect when agar dilution and broth dilution were compared (5,7,10,13,19). Our additional testing of ampicillin, ampicillinsulbactam, gentamicin, and imipenem suggests that we might have obtained better agreement of results between the Alamar system and the reference method if we had chosen broth microdilution as the reference method for all of the agents except imipenem.…”
Section: Discussionmentioning
confidence: 97%
“…The Alamar method tended to produce lower MICs than did agar dilution if the organism was very susceptible to the ,B-lactam agent but higher MICs if the organism produced an inducible or extended-spectrum r-lactamase. Other investigators have reported this dichotomous effect when agar dilution and broth dilution were compared (5,7,10,13,19). Our additional testing of ampicillin, ampicillinsulbactam, gentamicin, and imipenem suggests that we might have obtained better agreement of results between the Alamar system and the reference method if we had chosen broth microdilution as the reference method for all of the agents except imipenem.…”
Section: Discussionmentioning
confidence: 97%